Velocidades superluminais na relatividade geral: métrica de Alcubierre - Rodrigues, Douglas Benndorf [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The constancy of the speed of light appears to be an unbreakable barrier for future interstellar journeys, tending to infinite energy would be needed to achieve such speed. However in the general relativity one can circumvent this limit and get arbitrarily higher global speeds, without violating the constancy of the speed of light. The so-called “warp-drive metrics is a theoretical means to achieve global superluminal speeds. The Alcubierre metric is one case in which the science fiction inspired reality, from which was drawn the term “warp-drive. In the present work, a study of the theories of special and general relativity and of some works on solutions that allow superluminal speeds will be done

A constância da velocidade da luz aparenta ser uma barreira insuperá vel para as futuras viagens interestelares, energia tendendo a infinito seria necessária para alcançá-la. Mas com a relatividade geral pode-se driblar esse limite e obter velocidades globais arbitrariamente superiores, sem, no entanto violar a constância da velocidade da luz. As assim chamadas métricas de warp-drivesão um dos meios teóricos para alcançar velocidades globais superluminais. A métrica de Alcubierre é um dos casos em que a ficção científica inspirou a realidade, de onde foi tirado o termo warp-drive (motor de dobra). No presente trabalho, será feito um estudo das teorias da relatividade restrita e geral e de alguns trabalhos sobre soluções que permitem velocidades superluminais
Keywords: Relatividade geral (Fisica); Relatividade especial (Fisica); Luz - Velocidade; Calculo tensorial; Light Speed